The Influence of School Culture and Work Motivation on Junior High School Teachers' Performance - Unci Winarsih; M. Saroni; Nuruddin Araniri (Al-Ilmu, 2024)
This study aims to analyze the influence of school culture and work motivation on teacher performance at SMP Negeri 1 Tukdana, Indramayu Regency. Using a quantitative approach with an explanatory survey design, this study involved 57 teacher respondents selected through a saturated sampling technique. The research instrument was developed based on Robbins' (2018) theory for school culture, Herzberg's theory for work motivation, and Regulation of the Director General of Teachers and Education Personnel Number 7607 of 2023 for teacher performance. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0 software. The results showed that school culture had a positive and significant effect on teacher performance with a contribution of 72.42% (r = 0.851; t = 5.022 > 1.672). Work motivation also had a positive and significant effect on teacher performance with a contribution of 80.64% (r = 0.898; t = 7.713 > 1.672). Simultaneously, school culture and work motivation have a positive and significant effect on teacher performance with a contribution of 86.80% (R = 0.932; F = 178.133 > 2.19). This study provides an empirical contribution to the development of educational management theory and provides practical recommendations for improving teacher performance through developing school culture and increasing work motivation.